Strategies for Implementing Building Operability Certificate to Improve Performance of Building Management: A Case Study in Probolinggo City, Indonesia - Dwi Putranto Riau; null Rulinawaty; Dwi Siswahyudi; null Muhtarom (The Scientific World Journal)
An operability certificate is required before using a building. The building operability certificate concerns occupants’ safety before the building is used and is directed by Law Government Regulation 16 of 2021 for building security. This article discusses implementing a building operability certificate underperforming and the strategy for implementing the building operability certificate (SLF) policy. This research uses a descriptive qualitative method. First, qualitative data analysis utilizing SWOT determined the building operability certificate implementation strategy. Second, ranking strategies are analyzed to identify (QSPM’s) priorities. According to the regulation that every building must have SLF, the building operability certificate was not appropriately implemented. With the current building information system legislation, each region can issue Building Approval (PBG) and building operability certificate (SLF). Research findings based on SWOT and QSPM are used to generate seven strategies: Regional Apparatus Work Units (SKPD) commitment, increased socialization, regulation implementation, capacity building, optimal communication, SIMBG implementation, and increasing resources.